A clinical, randomized study on the influence of dental whitening on Streptococcus mutans population. (24th November 2017) - Briso, ALF; Silva, ÚAE; Souza, MBA; Rahal, V; Jardim Júnior, EG; Cintra, LTA
Abstract: Background: Dental whitening with peroxides has been popularized through the at‐home technique, which employs low concentrations of peroxide applied in individual trays. However, there are few clinical trials reporting the effects of its continuous use on oral microbiota. Thus, the purpose of the present clinical, randomized study was to evaluate the influence of at‐home whitening treatment on Streptococcus mutans in saliva, buccal mucosa, and subgingival and supragingival plaque. Methods: Thirty volunteers were randomly divided into two study groups ( N = 15) according to the whitening therapy: G CP, whitening using 10% carbamide peroxide 4 h daily for 21 days; and G HP, whitening using 6% hydrogen peroxide 1.5 h daily for 21 days. Samples from the predetermined locations were collected at three evaluation periods: T1, before; T2, immediately after; and T3, 30 days after the beginning of the treatment. The microbiological evaluation was made using conventional and molecular methods. Results: Student's t ‐test demonstrated a statistically significant decrease in S. mutans population in the subgingival and supragingival plaque for HP samples between T1 and T2 no difference was found between T1 and T3 regardless of the location and the whitening product used (α = 0.05). Conclusions: Although HP reduced S. mutans during treatment, the levels returned to baseline when assessed 30 days after the treatment.